Karakteristik Pasien Keratitis Herpes Simpleks Di PMN RS Mata Cicendo Periode Januari 2021-Desember 2021 - Sitti Fitriani; Elfa Ali; Angga Fajriansyah; Arief Akhdestira; Patriotika M (RS Mata Makassar: Journal of Ophthalmology, 2024)
Purpose : To describe characteristics of the patients herpes simpleks keratitis (HSK) at the National Eye Center Cicendo Eye Hospital Methods : Descriptive-retrospective study was obtained on electronic medical records from January to December 2021 at the National Eye Center Cicendo Eye Hospital Result : From total 121 patients (134 eyes) in this study, there were 60.3% male and 39.7% female. Patients mainly in the age group of 41-50 (30.6%). Bilateral HSK was found in 10.74% in present study. Type of HSK consist of epithelial in 31 eyes, non necrotizing stromal in 38 eyes, necrotizing stromal in 26 eyes, endotheliitis in 9 eyes, keratouveitis in 16 eyes, and neurotropik keratopathy in 14 eyes. Most of patients had visual acuity < 3/60, 44.03% and 37.31% early and last visit, respectively. 12.69% reccurance rate with the highest reccurance in stromal keratitis. Laboratory results showed that the most patients with Immunoglobulin G (IgG) (+) Immunoglobulin M (IgM) (-) anti HSV-1 were detected in 24 patients (19.83%). The treatment was acyclovir ointment, oral acyclovir,corticosteroid eyedrop and antibiotic eyedrop depend on type of HSK. Surgery was performed on 18 eyes, 9 eyes underwent amnion membran transplantation (AMT) patch graft, 8 eyes take lenticule+AMT patch graft and 1 eye reported takes evisceration. Conclusions : Majority type of HSK type were stromal keratitis followed by epithelial keratitis, neurotropik keratopathy, keratouveitis and endotheliitis. Reccurrance of HSK is common. Treatment depends on type of HSK and certain clinical conditions require surgery. Keywords : Herpes simplex keratitis, Characteristics, HSV-1